Usability and user satisfaction rate evaluation on e-learning application from student's perspective using Nielsen usability method - Alexander J P Sibarani (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2021)
Covid-19 is a new and contagious disease that has spread throughout the world community. This disease has spread to Indonesia since early March 2020. One way to prevent the spread of this virus is by implementing activities from home. Budi Luhur University is one of the educational institutions that has implemented work and learning from home during the Covid-19 pandemic. In the teaching and learning process, the E-Learning application is the main tool used both from the faculty and student sides. The total and urgent implementation of E-Learning application which began in March 2020 caused several problems that reduced the comfort of students in carrying out learning process. The purpose of this study is to measure the level of student satisfaction and the level of use of the E-Learning application and its features. This study used a survey sampling method by distributing questionnaires and getting results from 115 respondents. The method used in this research is the Nielsen Usability method. Measurements were made using five criteria: Learnability, Memorability, Efficiency, Errors, and Satisfaction. Result show, although the average of each dimension is in the satisfied interpretation, there are significant differences in the level of satisfaction in each dimension. The dimension with the lowest average rating is the Errors dimension. This shows that respondents still find some errors when using the E-Learning application so that respondents do not show significant satisfaction in terms of the Errors dimension. In other side, result shows that the respondent thinks face-to-face meetings are still needed.